#10 Variation in Antibiotic Use and Incidence of Surgical Site Infections in Pediatric Liver Transplant Recipients. (14th June 2022) - Kitt, Eimear
Abstract: Background: Surgical site infections (SSIs) are an important source of early complication after liver transplantation (LT). Peri-operative antibiotics to prevent SSI is considered standard of care, yet there are limited data on the frequency of SSI and no consensus on a standardized regimen. A major barrier is the lack of a large cohort of pediatric LT recipients. Leveraging merged data from the Pediatric Health Information System (PHIS) and the United Network for Organ Sharing (UNOS) we assembled a large cohort of pediatric LT patients to describe the frequency of SSI, variation in antibiotic prophylaxis practices and associated factors. Method: The source cohort included all patients under 18 years in the UNOS database who received a LT at a PHIS-participating institution between January 1st 2006 to August 6th, 2017. We excluded those undergoing multi-visceral transplantation and/or re-transplantation. Patient data were merged using a probabilistic merge algorithm using the following present in both datasets: transplant center, date of birth, gender and date of transplant. Our primary outcome was any SSI present during the first 30 days of the hospitalization in which the LT was performed. SSI was defined using ICD 9 and ICD-10 diagnosis codes for post-operative surgical site infection, in addition to procedure codes for incision and drainage or return to the operating room. Peri-operative prophylaxis regimens were inclusive of antibiotic(s) received on the day of or day after LT. After all unique antibiotic regimens were identified, we further categorized into 6 levels of clinically relevant antibiotic combinations ranging from narrowest (Level 1 was cefazolin) to broadest spectrum (Level 6 was carbapenems). Patients receiving agents from more than one category defaulted to the broadest spectrum group. Vancomycin/linezolid administration was collected as a distinct covariate. Data collected on baseline factors included age at LT, sex, race, specifics of the LT type, and severity of illness (SOI) defined as receiving ICU level care on at least one day in the week prior to LT. Results: Data from PHIS was successfully merged to 3055 (94%) of patients in the UNOS cohort. We excluded 264 multi-visceral transplants and/or re-transplants and 205 LT recipients without a categorizable antibiotic regimen with a final cohort of 2586 patients. This cohort was 50.8% female, 11.6% Black and 65% White with median age of 2 years (IQR of 0, 9). 11.6% of patients required at least one ICU level of care day in the week prior to LT and the median hospital stay from day of transplant was 20 days (IQR: 13, 35). An SSI was identified during the hospital stay in 284 (11%) patients. As we discovered that patients less than 1-year of age at transplant were almost twice as likely to experience an SSI compared to patients over 1 year (16.2% versus 8.6%), the distribution of other covariates by antibiotic category was assessed after stratifying <1 year versus >=1 year (Table 1A and Table 1B).Category 5 was the most commonly represented antibiotic group.Significant differences in antibiotic regimen included donor type and type of liver transplanted, receipt of dialysis the week prior, and in those meeting SOI criteria. In older patients, differences in antibiotics administered were additionally noted within race category and if there was concern for donor infection. Conclusion: SSI was common and varied by age, with children under one more likely to sustain an SSI. Antibiotic regimens administered varied withing each of these age groups. Factors associated broader-spectrum categories included receipt of a living donor LT, dialysis in the week prior to LT, and needing at least one ICU-level of care day in the week prior to LT. Additional multivariate analyses are warranted and will focus on investigating the degree to which center-specific differences are driving variation and will explore the comparative effectiveness of different antibiotic prophylaxis categories on SSI risk.